Literasi Fintech Syariah pada Mahasiswa: Analisis Kepatuhan terhadap Prinsip Syariah dan Risiko Perilaku Konsumtif - Sulaeman (Universitas Muhammadiyah Makassar, 2025)
The rapid development of financial technology has significantly influenced students’ financial behavior, including the increasing use of Islamic fintech services. However, this convenience also raises concerns regarding compliance with Islamic principles and the risk of consumptive behavior. This study aims to descriptively measure the level of Islamic fintech literacy and students’ compliance with sharia principles, as well as to statistically examine the effect of Islamic fintech literacy on students’ consumptive behavior. This research employed a quantitative approach with a descriptive–explanatory survey design. The participants were 124 students from the Faculty of Economics and Business at Universitas Muhammadiyah Makassar, selected using purposive sampling. Data were collected through a Likert-scale questionnaire and analyzed using descriptive statistics and simple linear regression. The results indicate that students’ Islamic fintech literacy is at a moderate to high level, while compliance with sharia principles is at a moderate level. Regression analysis reveals that Islamic fintech literacy has a negative and significant effect on students’ consumptive behavior. In conclusion, Islamic fintech literacy serves as an important protective factor in reducing consumptive tendencies and promoting more ethical and sharia-compliant financial behavior among students.